Drivers and performance outcomes of ecological export marketing strategies: a resource-based perspective - Leonidou, Leonidas C.; Fotiades, Thomas A.; Christodoulides, Paul (My University, 2012)
Despite the plethora of research on environmental marketing issues within the domestic marketing domain, studies on the subject are virtually absent in international marketing. However, there is evidence indicating that firms adopting ecologically-friendly marketing strategies are increasingly becoming more successful in international markets, as opposed to those following non-ecological foreign marketing practices. Our study sheds light on this important issue. Drawing on the resource-based view of the firm, we identify four organizational resources (physical, financial, research, scale) and four organizational capabilitie (relationship building, technology response, shared vision, cross-functional coordination) with a potential effect on building an environmentally-friendly export marketing strategy. The implementation of this strategy is hypothesized to have a positive effect on the exporter’s competitive advantage. The strength of the latter association is expected to be moderated by the degree of competitive intensity and environmental public concern within the specific foreign market in which the exporter operates. The model is tested on data from 202 exporters of manufactured goods. The results emphasize the importance of designing ecologically-friendly export marketing strategies in foreign markets, and have important implications for both export marketing managers and public policymakers
Keywords: Marketing; Consumers; Export marketing; Green marketing